Bio-Math Synergy: Creating Relevant Cross-Disciplinary Learning in the Digital Age - Fitri, Fitri; Hasbi, Muhammad (ETDC: Indonesian Journal of Research and Educational Review, 2025)
High school learning is generally divided into isolated subjects, with biology deemed rote learning and math as formulas with no practical value. In the data-driven digital age, high school students find it difficult to connect statistical or algebraic concepts to biological events like the spread of viruses and changes in ecosystems. Lack of connection between these fields reduces computational thinking and scientific literacy. This study examines whether the "Bio-Math Synergy" learning model improves high school students' transdisciplinary comprehension. The study used computerized techniques to incorporate ecology, genetics, function modeling, and basic statistics. This quasi-experimental study used pretest-posttest control groups. Eleventh graders from two Wajo Regency high schools studied. The experimental class utilized the "Bio-Math Synergy" model to analyze biology lab data through an interactive simulation platform and spreadsheets, while the control class employed traditional learning methods. The findings indicated the experimental class had much higher numeracy literacy results than the control class. Students learn that biology requires mathematics by modeling bacterial development and Mendel's rules digitally. Because STEM education felt more relevant to contemporary technology, an interest poll showed a 40% rise in student excitement for STEM jobs. This article provides a practical module for high school teachers to apply biology-math project-based learning (PjBL). This study supports digital-era education approaches that encourage critical thinking and cross-disciplinary problem-solving for Generation Z.